Grundfragen des Schadenersatzrechts aus rechtsvergleichender Sicht - Helmut, Koziol (Jan Sramek Verlag, 2014)
The volume contains the critical responses from the perspective of other legal systems to the propositions Helmut Koziol puts forward in 2012 in his book "Basic Questions of Tort Law from a Germanic Perspective". These reports not only describe the legal situation in selected legal systems, but also give a critical response to the propositions developed in respect of the Germanic legal family. Moreover, they consider the possible incorporation or rejection of the said propositions into the legal systems. This study is not only intended to promote mutual understanding between the individual legal systems but also to provide a basis for them to gradually grow together by means of both the internal development of the national legal systems and supranational elaboration of bodies of rules. English Version: http://e-book.fwf.ac.at/o:815